Oliver Heaviside’s Operational Calculus : The Foundations of Electrical Engineering [History] - Godoy Simões, Marcelo (IEEE, 2024)
Toward the end of the 19th century, Oliver Heaviside developed a formal calculus of differential operators to solve various physical problems. Oliver Heaviside was the man who wrote, for the first time in the history of science, the now-so-called Maxwell’s Four Laws of Electricity and Magnetism. Maxwell published his two-volume work, A Treatise on Electricity and Magnetism, in 1873.
Keywords: Biographies; Heaviside; Oliver; Calculus; Electricity; history; fi=Sähkötekniikka|en=Electrical Engineering|